Maritime Boundaries in the North Sea: a Review - Elema, Ina; Jong, Kees de (The International Hydrographic Review, 2001)
In this paper an overview is given of the geodetic factors that should be taken into account when defining boundaries at sea. Particular attention is given to the North Sea, a sea surrounded by a relatively large number of countries. First, differences between several geodetic and vertical (chart) datums and their international standardisation on nautical charts are considered. Next, precision and reliability aspects of computed median lines are discussed. Attention in a technical way is given to the United Nations Convention on the Law of the Sea (UNCLOS) in relation to national rules and regulations. For The Netherlands in particular, this includes the mining legislation for the continental shelf, the fishing legislation and the regulations with regard to large infrastructural works. Finally, some recommendations will be given to preclude future ambiguities in boundaries at sea.